2016
DOI: 10.1523/jneurosci.1244-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Control of Drinking Behavior by Median Preoptic Neurons in Mice

Abstract: Stimulation of glutamatergic neurons in the subfornical organ drives drinking behavior, but the brain targets that mediate this response are not known. The densest target of subfornical axons is the anterior tip of the third ventricle, containing the median preoptic nucleus (MnPO) and organum vasculosum of the lamina terminalis (OVLT), a region that has also been implicated in fluid and electrolyte management. The neurochemical composition of this region is complex, containing both GABAergic and glutamatergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 34 publications
3
80
0
Order By: Relevance
“…III.10). However, we can not completely exclude the possibility that the SFO→MnPO pathway was also involved in the control of water intake (Abbott et al, 2016).…”
Section: Iii4 Discussionmentioning
confidence: 88%
“…III.10). However, we can not completely exclude the possibility that the SFO→MnPO pathway was also involved in the control of water intake (Abbott et al, 2016).…”
Section: Iii4 Discussionmentioning
confidence: 88%
“…Our experiments showed that activation of glutamatergic MnPO neurons decreases core temperature substantially, an effect we attributed to cutaneous vasodilatation. In addition to hypothermia, in many animals stimulation also caused water consumption [3], which we found was due to activation of a largely separate set of glutamatergic neurons in the more dorsal part of the MnPO. The hypothermic effect, by contrast, was due to activation of glutamatergic neurons in the avMNPO.…”
mentioning
confidence: 70%
“…How glutamatergic MnPO neurons regulate cutaneous blood flow is unclear as these excitatory neurons innervate several brain regions that are thought to promote heat conservation by regulating sympathetic outflow to cutaneous vasoconstrictor neurons (CVC) [3]. One possible route would be that direct projections from glutamatergic MnPO neurons to the DHA/DMH, and the medullary raphe and parapyramidal region, may represent inputs to local inhibitory neurons within these targets that modulate the activity of sympathoexcitatory output neurons [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the neurons in these three sites in the lamina terminalis that were activated by intravenous infusion of hypertonic saline were shown to be directly connected to the vasopressin secreting neurons of the supraoptic and paraventricular nuclei (Oldfield et al, 1994;McKinley et al, 2004) and relayed via thalamic sites to cortical regions involved in the genesis of thirst (Hollis et al, 2008). Recent studies in mice using optogenetic techniques to stimulate or inhibit neuronal populations within the lamina terminalis confirm the importance of the lamina terminalis in regulating water intake (Abbott et al, 2016;Zimmerman et al, 2016).…”
Section: Influences Of Brain Regions Mediating Osmoreceptor On Thirstmentioning
confidence: 89%